A post-starburst pathway for the formation of massive galaxies and black holes at z > 6 - Onoue, Masafusa; Ding, Xuheng; Silverman, John D.; Matsuoka, Yoshiki; Izumi, Takuma; Strauss, Michael A.; Ward, Charlotte; Phillips, Camryn L.; Ito, Kei; Andika, Irham T.; Aoki, Kentaro; Arita, Junya; et al. (Nature astronomy, 2025)
Understanding the rapid formation of supermassive black holes in the early Universe requires insights into stellar mass growth in host galaxies. Here we present NIRSpec rest-frame optical spectra and NIRCam imaging from JWST of two galaxies at z > 6, both hosting moderate-luminosity quasars. These galaxies exhibit Balmer absorption lines, like low-redshift post-starburst galaxies. Our analyses of the medium-resolution spectra and multiband photometry show that the bulk of the stellar mass (log(M*/M☉) ≥ 10.6) formed in starburst episodes at redshift 9 and 7. One of the galaxies shows a clear Balmer break and lacks spatially resolved Hα emission. It falls well below the star-formation main sequence at z = 6, indicating quiescence. The other is transitioning to quiescence; together, these massive galaxies are among the most distant post-starburst systems known. The blueshifted wings of the quasar [O iii] emission lines indicate quasar-driven outflow, which possibly influences star formation. Direct stellar velocity dispersion measurements reveal that one galaxy follows the local black hole mass versus σ* relation whereas the other is overmassive. The existence of massive post-starburst galaxies hosting billion-solar-mass black holes in short-lived quasar phases indicates that supermassive black holes and host galaxies played a principal role in each other’s rapid early formation.
Online veröffentlicht: 11. August 2025
Gesehen am 22.01.2026